Gliosarcoma arising from oligodendroglioma, IDH mutant and 1p/19q codeleted. Issue 1 (15th August 2017) - Yasuda, Takayuki; Nitta, Masayuki; Komori, Takashi; Kobayashi, Tatsuya; Masui, Kenta; Maruyama, Takashi; Sawada, Tatsuo; Muragaki, Yoshihiro; Kawamata, Takakazu
Abstract : Herein, we present a rare case of gliosarcoma arising from oligodendroglioma, isocitrate dehydrogenase ( IDH ) mutant and 1p/19q codeleted. A 36‐year‐old man presented with a non‐enhanced calcified abnormal lesion on the right frontal lobe. The patient underwent subtotal surgical resection, PAV chemotherapy (procarbazine, nimustine (ACNU) and vincristine), and fractionated radiotherapy with 50 Gy. The pathological diagnosis was oligodendroglioma, IDH mutant and 1p/19q codeleted, World Health Organization 2016 grade II. Six years later, a new enhanced lesion appeared, and the recurrent tumor was surgically removed. Although the histopathological findings indicated gliosarcoma, the recurrent tumor still demonstrated the IDH mutation and 1p/19q codeleted. Thus, the recurrent tumor was considered to originate from oligodendroglioma, rather than being newly generated after chemoradiotherapy. Interestingly, the second recurrent tumor responded well to temozolomide chemotherapy. Based on the findings of this case, oligodendrogliomas have the potential for mesenchymal transformation on progression, while keeping their genotype.